Characteristics of lung cancer after a previous malignancy - Reinmuth, Niels; Stumpf, Patrick; Stumpf, Andreas; Muley, Thomas; Kobinger, Sonja; Hoffmann, Hans; Herth, Felix; Schnabel, Philipp Albert; Bischoff, Helge; Thomas, Michael (Respiratory medicine, 2014)
Background - In the era of improving overall survival rates of malignant diseases, the impact of a previous malignancy (PM) on treatment and outcome of lung cancer (LC) remains unclear. - Methods - We reviewed all LC patients from our institution that were treated from 2004 to 2006 for the occurrence of LC with PM excluding patients with multiple primary LC. - Results - A total of 444 and 2698 LC patients with and without a history of a PM were identified (prevalence of 14.1%). PM were most often located in breast (15.5%), prostate (14.9%), bladder (9.0%) and kidney (8.8%). Compared to never smokers, patients with nicotine consumption had more often a cancer history of prostate, gastrointestinal, and the head-neck region. The median interval until diagnosis of LC was 72.2 months (range 0-537 months) with most LC diagnosed 5 years after PM diagnosis. With a similar distribution of histology, stage and localization compared to controls, NSCLC patients with PM and stage IV disease showed a favorable overall survival (p < 0.0001). In contrast, SCLC patients had similar survival curves (n.s.). - Conclusions - A considerable subgroup of LC patients has a history of PM that may indicate a favorable prognostic factor. However, these patients should be treated similar to other LC patients.